SMART Pharmacist—The Impact of Education on Improving Pharmacists’ Participation in Monitoring the Safety of Medicine Use in Montenegro - Snežana Mugoša; Arijana Meštrović; Veselinka Vukićević; Milanka Žugić; Michael J. Rouse (Pharmacy)
Pharmaceutical care as a concept was introduced in Montenegro during the last 10 years. The Pharmaceutical Chamber of Montenegro (PCM) and the Institute for Medicines and Medical Devices (CInMED) conducted SMART Pharmacist Program educational activities for pharmacists as a project to improve their impact on monitoring drug safety. In the period from September 2023 to May 2024, a total of 78 pharmacists participated in the project, of which 53 (68%) submitted valid reports of suspected adverse drug reactions (ADRs). During the project, a total of 302 valid reports were submitted, and the pharmacists’ share in total reporting increased to 74% in 2023 compared to less than 10% in the previous 5 years. The results of this research will be used to make recommendations for further improvement of the pharmacovigilance system, as well as to create plans for continuing education (CE) of other health workers in the area of rational and safe use of medicines.